2007
DOI: 10.1002/mar.20199
|View full text |Cite
|
Sign up to set email alerts
|

Ad framing effects for consumption products: An affect priming process

Abstract: This research examines why positively framed messages work more effectively than negatively framed messages in product advertising by establishing an affect priming process model. Findings from Experiment 1 showed that positively framed ad messages evoked higher levels of positive affect and lower levels of negative affect than did negatively framed ad messages. Accordingly, positively framed ad messages generated more favorable ratings on ad believability, ad liking, and brand attitudes. Most importantly, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 57 publications
2
40
1
Order By: Relevance
“…A more valuable contribution of this study is empirical evidence supporting negative affect as a mediator in the relationship between message framing and public policy support in the context of goal framing. Consistent with previous research (Chang, 2008;Shen & Dillard, 2007), we found that the loss frame induced greater negative affect than the gain frame. More notably, mediation analysis also supported the hypothesis that the impact of goal framing on public policy support was fully mediated by negative affect.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A more valuable contribution of this study is empirical evidence supporting negative affect as a mediator in the relationship between message framing and public policy support in the context of goal framing. Consistent with previous research (Chang, 2008;Shen & Dillard, 2007), we found that the loss frame induced greater negative affect than the gain frame. More notably, mediation analysis also supported the hypothesis that the impact of goal framing on public policy support was fully mediated by negative affect.…”
Section: Discussionsupporting
confidence: 92%
“…Since Shen and Dillard's (2007) study demonstrating that gain-framed messages led to greater positive emotions, and loss-framed messages led to greater negative emotions, research in the area of health communication has persisted (Chang, 2008;O'Keefe & Nan, 2012;Wong, Harvell, & Harrison, 2013). These findings are consistent with appraisal theories of emotion.…”
Section: Affect As An Intervening Variablementioning
confidence: 55%
“…Valenced frame, implicitly bearing positive versus negative attributes, highlights opposite aspects of factually identical situations or objects (de Vreese & Boomgaarden, 2003, p. 363), such as gain or loss, advantage or disadvantage, favor or disfavor, leading to frame-cued evaluation and assessment among audience. Many studies support the hypothesis that valence framing has significant influence on people's perception, judgment and decision-making in various sub-fields of communication (e.g., Chang, 2005Chang, , 2008Levin & Hart, 2003;Rothman & Salovey, 1997;Schuck & de Vreese, 2006;Wang, 2007).…”
Section: Image and Product-related National Imagementioning
confidence: 94%
“…Furthermore, Chang (2008) and Tu et al (2013) have proposed that green advertising messages can influence customers' views and judgments about products as suggested by several researchers (Qader and Zainuddin, 2011;Zhu, 2012, Nyborg et al 2006.…”
Section: Green Advertising Eco-labeling and Adoption Of Ecological Pmentioning
confidence: 99%